ENHANCEMENT VERBAL ABILITY OF STUDENTS ON MATHEMATICS LEARNING USING GROUP LEARNING MODELS OF STUDENTS CLASS VIII IN MTs AL MU'MIN - Gusnanda Adi Purwono; Sunaryo Sunaryo (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
The verbal ability of grade VIII students of MTs Al Mu'min Temanggung Islamic Junior High School Academic Year 2017/2018 on learning mathematics was still lacking. This research aimed to increase students' verbal ability on mathematics learning using group learning models of students class VIII in MTs Al Mu'min Temanggung on even semester in 2017/2018. Â This research is a Classroom Action Research. The setting use class VIII-A with 30 students. The research was conducted two cycles by using group learning models. The method of data collection using observation, interview, and documentation. The instrument research using observation sheet and interview guidelines. The instrument analyzes using content validity. The analysis used in the research is a qualitative descriptive analysis. This research showed that learning by using group learning models can increase students' verbal ability to learn mathematics in class VIII-A of MTs Al Mu'min Temanggung Islamic Junior High School Academic Year 2017/2018. These things were proven by observing the student's verbal ability to learning in every cycle has increased. The average percentage of observations resulting from students' verbal ability on the first cycle was 43.33% with enough criteria, and on-cycle II, it increases to 62.33% with good criteria. The results of interviews with students showed a positive response to the student's verbal ability.